Preparation and thermophysical properties of Lu3TaO7. Issue 11 (1st June 2022) - Sang, Weiwei; Zhang, Hongsong; Chen, Huahui; Guo, Yihao; Ling, Jinlong; Chen, Xiaoge; Xie, Wenbo
Abstract: Lu3 TaO7 was prepared through a modified sol-gel technique and high-temperature sintering method to investigate its lattice type, micro-morphology, phase stability, thermal expansion coefficient, and conductivity. The results indicate that the obtained powder and bulk samples are composed of a single fluorite structure. The obtained bulk sample shows a dense microstructure, and uniform element distribution. The thermal conductivity of the Lu3 TaO7 oxide slightly increases with temperature due to typical amorphous-like behaviour, which is much lower than those of 7 wt% yttrium oxide–stabilized zirconium oxide (7YSZ) and Sm2 Zr2 O7 ceramics. Furthermore, the enhanced phonon scattering leads to a lower thermal conductivity of Lu3 TaO7 than that of Gd3 TaO7 . The thermal expansion coefficient of the Lu3 TaO7 oxide reaches 10.72 × 10 −6 K −1 at 1200 °C, which is slightly greater than that of 7YSZ. The outstanding phase stability up to 1200 °C satisfies the requirements for thermal barrier coatings.